Factors that influence the choice of contraceptives in women - e Cunha, Rebeca de Sousa (2022)
Introduction: The choice of contraceptive method in women of childbearing age is accompanied by a set of fears and constraints. Objectives: To identify factors that influence the choice of contraceptive method, in a group of women of childbearing age and discuss possible strategies to be used by the family physician, aiming at an informed choice. Methods: Firstly, a literature review was performed by searching the PubMed electronic database, limited to the period between 2010 and 2019, using the key: ‘contraception’ OR ‘family planning’ AND ‘selection criteria’. Subsequently, an observational and descriptive study was conducted in September 2019 in three Family Health Units in central Portugal. Women of childbearing age, with scheduled family planning consultation, were the target population. The sample was randomly selected (n=127). These women answered a questionnaire that allowed the collection of personal data such as age, marital status, and prior pregnancies, as well as their quantitative assessment against a list of factors that could influence their decision about the choice of a contraceptive method. Results: The oral hormonal contraceptive was the most used method (57.5%), while the effectiveness (78%) and safety of the method (78.7%) were considered very important factors. Less prominently, women reported the following factors: ease of use (59.8%), preventing irregular blood loss (55.9%), protecting against sexually transmitted diseases (54.3%), accessibility (53.5%), and avoiding side effects (53.5%). Regarding the opinion of third parties, only the opinion of the doctor was considered very important for 59.1% of them. Conclusion: This study allowed the identification of a set of factors considered relevant for women of childbearing age when choosing a contraceptive method. These results may help family physicians direct their approach, answering their questions and concerns so that later they can make their individual decision on which method to use.